Projected benefits of CGIAR Research - Prager, Steven D.; Kruseman, Gideon K. (2022)
This report focuses on identifying plausible futures and potential returns on investment in the form of projected benefits for the One CGIAR research portfolio. Literature reviews indicate that returns are high. One meta-analysis of 292 studies finds an average rate of return of 100% on agricultural research after excluding extremely high outliers. In another study of 84 counties, the authors estimate that a 10-percentage-point increase in adoption of high-yielding varieties increases gross domestic product (GDP) per capita by about 15%. While macro-level returns on investment in agricultural research are clear, evidence linking technology adoption to improved agricultural productivity at the farm level is more difficult to find; studies are underway to enable estimations of returns on investment for specific crops and the corresponding socio-technical bundles.